Steric And Eustatik Effect Contributions To Sea Level Change Based On Altimetry Satellite Argo And Grace Satellite Data Within 1992-2012 Period (The Study Area: The Western Pacific Ocean) - Hartanto, Prayudha; Lestari Nurmaulia, Sella; Prijatna, Kosasih (Indonesian Journal of Geospatial, 2013)
Abstract. The change of sea level in the western Pasific Ocean is one of the biggest change in the world. This is caused by steric and eustatic factors. In the period of 1992-2012, the total change of sea level in this area based on the Topex/Poseidon satellite data, Jason 1 and Jason 2, was 6. 982 Â± 3.493 mm/year. Based on the temperature and salinity from Argo floats for the period 2000 â 2013, Â the obtained high streic changes in sea level in the region is about 14.352 Â± 13.002 mm/year. The result is a based on high steric sea level relative to 900 dbar pressure. To find the rise of eustatic sea level that caused by the changes in ocean mass, linear regression performed on the data Equivalent Water Thickness (EWT) of monthly GRACE satellites in the period January 2004 to April 2013. The magnitude of the linear trend EWT changes in this area is -0.4026 Â± 0.1073 mm/year. This study concludes that the correlation between EWT and the SLA value is more significant than the correlation between high steric sea level and SLA. But further investigation is needed to determine the factor that contributes more to changes of sea level in the study area. This occurs due to the presence of still considerable correlation between the high steric sea level and ocean mass which is the independent variable in the equation of total sea level . To minimize these correlations , observations required high steric and ocean mass with a longer time span.Â Keywords : The change of sea level, steric, eustatic, the western Pasific Ocean, linear trendÂ